Atomic Force Microscopy of host cell-amastigote interaction in cutaneous leishmaniasis - Lugo de Yarbuh A; Colasante C; Alarcón M; Moreno E (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
Abstract: Natural infection produced by the entry of promastigotes into the skin cells induces cutaneous leishmaniasis disease and the Interaction between phagocytic cells and different strains of Leishmania determine the course of disease in the mammalian host. In this study the cutaneous lesions from hamsters infected with the L. garnhami were pressed on a microscope slide, allowed to dry and methanol-fixed in order to be ultrastructurally analyzed using atomic force microscopy (AFM). Free amastigotes showed their nucleus, kinetoplast and a depression of 5 microns, corresponding to the refractil organelle characteristic of this Leishmania. Parasites inside macrophages and lymphocytes and the topographical relationship with the host cytoplasm was also observed. Parasite-host-cell interaction revealed different membrane contact. The amastigote-macrophage contact is established by small macrophage filopodio associated with its cytoplasmic reduction near the contact site of 800 nm. The amastigote-lymphocyte contact shows fusion-like behavior between the two membranes without any cell specialization. The cutaneous lesion studied with AFM allowed observation with high resolution the close contact established between the parasite and its host cells as well as details of the fine structure of the amastigotes, applying a simple and rapid tissue preparation. Resumen: La infección natural producida por la entrada de promastigotes en la piel produce leishmaniasis cutánea y la interacción entre las células fagocíticas y las diferentes cepas de Leishmania determina el curso de la enfermedad en el hospedador vertebrado. En este estudio las lesiones cutáneas de hamsteres infectados con L. garnhami fueron frotadas sobre un portaobjeto, secadas a temperatura ambiente y fijadas con metanol para analizarlas ultraestructuralmente usando un microscopio de fuerza atómica (AFM). Los amastigotes mostraron el núcleo, kinetoplasto y una depresión de 5µ, correspondiente a la organela refráctil característica de esta especie. Los parásitos dentro de los macrófagos y de linfocitos y las relaciones topográficas con el citoplasma de la célula hospedadora, revelaron diferentes tipos de contacto entre las membranas celulares. El contacto amastigote-macrófago se establece por un pequeño filopodio del macrófago asociado con reducción citoplasmática cerca del sitio de contacto de 800 nm. El conctato amastigote-linfocito mostró estrecha fusión entre las dos membranas sin ninguna especialización celular. Concluimos que las lesiones cutánes estudiadas con AFM permite la observación con alta resolución, del estrecho contacto que se establece entre los parasites y sus células hospedadoras así como, los detalles de la ultraestructura de los amastigotes aplicando una simple y rápida preparación de las muestras de tejido.